Environmental Exposures and Polycystic Ovary Syndrome: A Review - Peebles, Elizabeth; Mahalingaiah, Shruthi (Seminars in Reproductive Medicine, 2024)
Polycystic ovary syndrome (PCOS) is the most common heterogeneous endocrine disorder in women of reproductive age, affecting around 5 to 10% of women and up to 21% depending on the applied diagnostic criteria and study population. People with PCOS may experience oligomenorrhea, androgen excess, and polycystic ovary morphology. The etiology of the disease is not completely understood, with genetics, epigenetics, endocrine, metabolic, lifestyle, and environmental factors contributing to its development and severity. Environmental exposures are an important, burgeoning field in menstrual research, as they potentially link to menstrual cycle disruption and the risk of reproductive disorders such as PCOS. This review examines the recent research investigating environmental exposures—air pollution, micro- and nanoplastics, heavy metals, and endocrine-disrupting chemicals—and PCOS in human and animal models, concluding with potential mechanisms, limitations, and considerations for future work. Overall, research on environmental exposures and PCOS is limited and yields heterogeneous results across studies. Specifically, exposures such as air pollutants, micro- and nanoplastics, persistent organic pollutants, and parabens have noticeably limited research. Future research can help fill the gap in understanding how environmental exposures, particularly across gestational, childhood, and reproductive adult life stages, may impact PCOS.
Keywords: environmental exposures; polycystic ovary syndrome; endocrine-disrupting chemicals; microplastics; per- and polyfluoroalkyl substances